Influence of the propagation of three phase contact line on flotation recovery - Subasinghe, Nimal; Albijanic, Boris (Elsevier, 2014)
Froth flotation is considered the most effective process of beneficiating low grade ores and is widely used in the base metals industry. For effective flotation, the attachment of mineral particles to air bubbles is important and has been studied by many researchers by measuring quantities such as attachment time, film-thinning time and induction time. This paper identifies an important step in the bubble–particle attachment process, namely, the expansion mechanism of the three phase contact (TPC) line between liquid, solid and air. It has been shown that the TPC expansion time is determined by the drainage of the surrounding fluid. It is influenced by factors such as pulp chemistry surrounding the particle, variations in surface forces and pressure inside the bubble. It has been observed experimentally that the TPC expansion time bears square root relationship to attachment efficiency. In this work, it has been argued that the attachment efficiency is related to the TPC circle radius propagation.